Catalytic influence of iron loaded sba-15 for the photodegradation of congo red dye - A.R. SASIEEKHUMAR; T.SOMANATHAN; M. SHANMUGAM (International Journal of Pharma and Bio Sciences, 2017)
A series of iron loaded SBA-15 was prepared by simple impregnation method using ferric nitrate as a metal precursor and tetra ethyl orthosilicate as a silica source. The metal loaded SBA-15 was confirmed by various characterization techniques such as x-ray diffraction (XRD), N2 sorption studies, scanning electron microscope (SEM) and transmission electron microscope (TEM). The results of XRD, nitrogen sorption and TEM indicate the formation of highly ordered hexagonal structures of mesoporous materials. Photodegradation of congo red (CR) were studied using Fe/SBA-15 under direct sunlight and analyzed the samples by UV visible spectrophotometer. The degradation efficiency of CR was observed within 90 min and the optimization studies were also done systematically.